Histoenzymic distribution of alkaline and acid phosphatases in the ovary of buffalo (Bubalus bubalis) with age - BHARDWAJ, R L; ROY, K S (The Indian Journal of Animal Sciences, 2014)
The study was conducted on the ovaries of 46 (neonatal 13, prepubertal 3, cyclic 22,and pregnant 8) normal healthy Murrah female buffaloes. The fresh ovarian tissues were coliected in the liquid nitrogen for the histoenzymic demonstration of AKPase and ACPase. The tissues were put to cryostat at -20Â°C to obtain sections at 1 0 Âµm on clean glass slides and incubated for phosphatases activity. Histoenzymic study revealed high contents of AKPase and ACPase in primordial, primary secondary and Graafian follicles as compared to atretic follicles. The luteal and interstitial gland cells had high contents of AKPase and ACPase activity.